ANALISIS PENGARUH DAYA TARIK KULINER MALAM TERHADAP MINAT BERKUNJUNG DI PASAR LAMA TANGERANG - Angelina, Grecia; Andari Tirtadidjaja (Bajang Institute, 2024)
Pasar Lama Tangerang is an area in Tangerang City. This research was conducted to determine whether or not there was an influence of the attractiveness of night culinary delights on interest in visiting Pasar Lama Tangerang. This research uses quantitative methods using data analysis, mean descriptive statistical tests, validity tests, reliability tests, classical assumption tests, hypothesis tests using the t test and coefficient of determination tests. The test used data from 100 samples as respondents from Pasar Lama Tangerang. Based on the results of research that has been carried out, the average value of variable Based on the t test calculation, it produces a significance value of 0.000 below 0.05 which can be concluded that variable in the coefficient of determination test which produces a value of 0.582, it can be stated that variable X (Attraction of Night Culinary) has an influence of 58.2% on variable Y (Intention to Visit). The simple linear regression test produces a value of 0.431, so it can be stated that culinary attractiveness has a positive effect on interest in visiting Pasar Lama Tangerang.